VERBAL AND NONVERBAL LANGUAGE: PRE-SERVICE TEACHERS’ DECISIVENESS IN TEYL - Astutik, Yuli; Purwati, Oikurema (Universitas Pendidikan Indonesia, 2021)
The ability to communicate in the classroom is an essential point for teachers to convey lessons material well. Some experts state that communication is a form of verbal and nonverbal language. This study analyzes how pre-service teachers prepare to become professional English teachers in teaching English as a foreign language. By using two different theories, Brown (2007) and Hall (1959), the researchers investigate the extent to which pre-service teachers use verbal and non-verbal language in the practice of teaching English to elementary students. In collecting data, researchers conducted observations and interviews to research subjects. The researchers then analyzed the data in several stages and made conclusions. In a nutshell, all pre-service teachers with different levels, low and competent, use verbal and nonverbal language during their teaching practice. However, they have different academic contributions to their performance in teaching English to young learners.